IMPACT OF THE CONSTRUCTION OF THE SARAMIRIZA-IQUITOS ROAD ON FORESTS AND PETLANDS IN THE RIO TIGRE, LORETO, PERU - HONORIO CORONADO, Eurídice (2020)
New infrastructure that seeks to connect Iquitos with Saramiriza includes building a ~350-km paved road alongside the Tigre river in Loreto. This project is a threat to the conservation of one of the largest areas of tropical forest on the planet and the largest and deepest peatlands in the Amazon basin. In this study, focused on the second section of the proposed road (Huambé – Marsella), we used a “business-as-usual” scenario (BAU) and a “road” scenario to show that road construction would lead to substantial loss of forest cover and increase CO2 emissions. The current loss of forest cover in a buffer zone of 20 km around the Huambé-Marsella road, estimated up to 2018, was 3.4 %. Using a multi-layer perceptron (MLP) neural network, we estimated deforestation of 80 071.11 ha and emissions of 35.55 Mt CO2 -eq for the period 2019-2064 in the BAU scenario, while the scenario with the construction of the road would generate greater loss of forests (303 248.79 ha) and higher emissions (135.56 Mt CO2 -eq). Avoiding the construction of the road alongside the Tigre river would therefore prevent the loss of 83 462.58 ha of forests and the emission of 41.49 Mt CO2 -eq from 2019 to 2030. Therefore, the Peruvian government should assess alternative proposals for transportation in this area. For example, improved fluvial boat services could be used for the transport of cargo and people, while an air taxi service could also help to meet the needs of indigenous communities and riverine settlers. Compliance with international commitments to reduce greenhouse gas emissions will potentially be impossible if the road is constructed as it is estimated that will increase national emissions by 1.31 % from 2019 to 2030. The funds saved from not constructing the road could subsidize the use of a modern river fleet, the air taxi service and the implementation of conservation strategies and sustainable management of the Amazonian forests and peatlands of the Tigre river.